GM1 Ganglioside Inhibits β-Amyloid Oligomerization Induced by Sphingomyelin - Amaro, Mariana; Šachl, Radek; Aydogan, Gokcan; Mikhalyov, Ilya I; Vácha, Robert; Hof, Martin (Angewandte Chemie (International ed. in English), 2016)
β-Amyloid (Aβ) oligomers are neurotoxic and implicated in Alzheimer's disease. Neuronal plasma membranes may mediate formation of Aβ oligomers in vivo. Membrane components sphingomyelin and GM1 have been shown to promote aggregation of Aβ; however, these studies were performed under extreme, non-physiological conditions. We demonstrate that physiological levels of GM1 , organized in nanodomains do not seed oligomerization of Aβ40 monomers. We show that sphingomyelin triggers oligomerization of Aβ40 and that GM1 is counteractive thus preventing oligomerization. We propose a molecular explanation that is supported by all-atom molecular dynamics simulations. The preventive role of GM1 in the oligomerization of Aβ40 suggests that decreasing levels of GM1 in the brain, for example, due to aging, could reduce protection against Aβ oligomerization and contribute to the onset of Alzheimer's disease.
Keywords: Alzheimer's disease; simulace molekulární dynamiky; amyloid beta-peptides; diffusion coefficients; neuroprotectives; G(M1) gangliosid; G(M1) Ganglioside; Sphingomyelins; Amyloid beta-Peptides; Molecular Dynamics Simulation; fluorescence spectroscopy; sfingomyeliny; amyloidní beta-protein